Success and Failure of African Exporters - Cadot, Olivier (The World Bank, 2011)
Using a novel dataset with transactions level exports data from four African countries (Malawi, Mali, Senegal and Tanzania), this paper uncovers evidence of a high degree of experimentation at the extensive margin associated with low survival rates, consistent with high and middle income country evidence. Consequently, the authors focus on the questions of what determines success and survival beyond the first year and find that survival probability rises with the number of firms exporting the same product to the same destination from the same country, pointing towards the existence of cross-firm synergies. Accordingly the evidence is consistent with the hypothesis that those synergies may be driven by information spillovers. More intuitively and consistently with multi-product firms models, the analysis also finds that firms more diversified in terms of products, but even more in terms of markets, are more likely to be successful and survive beyond the first year